(untitled) (GAIMS Journal of Medical Sciences, 2023)
Splenic abscess is a rare complication of thalassemia major. It has a high mortality due to delay in diagnosis and treatment. Medical treatment alone is insufficient and splenectomy is considered to be a gold standard for splenic abscesses. In this paper, we report a 22-year-old thalassaemic male with splenic abscess. He presented with moderate pain in left hypochondrium and tender splenomegaly. The diagnosis was confirmed by ultrasonography and computerized tomography scan and histopathology.